2017
DOI: 10.1186/s40795-016-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and nutritional adequacy of under-fives in a fishing community in the central region of Ghana

Abstract: Background: The irreversible effect of malnutrition on children as a result of micronutrient deficiency is of great public health concern. Micronutrient malnutrition is caused by the chronic lack of vitamins and minerals in diets. Dietary assessment is one of the ways in assessing micronutrient malnutrition. This assessment provides information about the quality of food consumed in terms of nutrient adequacy of children under five years in Ekumfi Narkwa, a fishing community along the Central regional coastline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 16 publications
4
37
4
Order By: Relevance
“…We found that while fish was the most commonly consumed animal-source food by mothers, fish was not introduced to the diets of infants and young children until they approach 18 months or two years of age. This finding differs from that of Bandoh and Kenu [61], who found a higher level of fish consumption among children in fishing communities in Ghana, but similar to Thorne-Lyman, Valpiani et al [62]'s study of fish-farming households in rural Bangladesh where animal-source foods (fish and meat) were withheld from the diets of infants and young children. Socio-cultural practices, including gender norms, and food taboos are recognised as affecting whom within a household receives different foods, and portions thereof, and, as we found here, this can particularly affect pregnant and lactating women and young children [63].…”
Section: Discussioncontrasting
confidence: 85%
“…We found that while fish was the most commonly consumed animal-source food by mothers, fish was not introduced to the diets of infants and young children until they approach 18 months or two years of age. This finding differs from that of Bandoh and Kenu [61], who found a higher level of fish consumption among children in fishing communities in Ghana, but similar to Thorne-Lyman, Valpiani et al [62]'s study of fish-farming households in rural Bangladesh where animal-source foods (fish and meat) were withheld from the diets of infants and young children. Socio-cultural practices, including gender norms, and food taboos are recognised as affecting whom within a household receives different foods, and portions thereof, and, as we found here, this can particularly affect pregnant and lactating women and young children [63].…”
Section: Discussioncontrasting
confidence: 85%
“…Again, a study in Ghana on dietary diversity in a fishing community revealed that there is an abundance of animal protein in especially from sea food and staples in their diet [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly sixty-four percent of the children met the minimum dietary diversity recommendation with an average dietary diversity score of 3.6. A study among children under five years in the Central region of Ghana however reported lower minimum dietary diversity scores [23]. Dietary diversity score was associated with higher mean WHZ and lower HAZ of children.…”
Section: Discussionmentioning
confidence: 99%